Proportional reinsurance for fractional Brownian risk model - Kępczyński, Krzysztof (Reasekuracja proporcjonalna w ułamkowo brownowskim modelu ryzyka, 2020)
This paper investigates the ruin probabilities for a two-dimensional fractional Brownian risk model with a proportional reinsurance scheme. The author focused on the joint and simultaneous ruin probabilities in a finite-time horizon. The risk processes of both insurance and reinsurance companies are composed of a large number of i.i.d. sub-risk processes, representing independent businesses. The asymptotics were derived as the initial capital tends to infinity
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2020, Nr 18 (24), s. 149-162